Energy Consumption and Economic Growth in Kazakhstan: A Causality Analysis Using Time Series Methods - Mutaliyeva, Aigul; Kazanbayeva, Zhanar; Balabekova, Dina; Abdullayev, Akikat; Mukhamedkhanova, Ainur; Yermakhanov, Yerkin (International Journal of Energy Economics and Policy, 2025)
This study examines the relationship between economic growth and energy consumption in Kazakhstan. Using data from 1995 to 2023, we analyze the relationship between GDP, total final energy consumption (TFEC), electricity use, and the share of renewable energy sources. The results of the analysis show that all variables are non-stationary over time, but only their changes are stable. This allowed us to test the long-term relationship. The Johansen cointegration test proved that there is a long-term equality between GDP and energy consumption in Kazakhstan: that is, as the economy grows, energy demand also increases. Electricity and the share of renewable energy are also related to GDP in the long run, but since the share of renewable energy is too small, its impact is not yet clear. Granger causality analysis showed that there is a bidirectional relationship between energy consumption and GDP. As the economy grows, energy consumption increases, and energy availability increases economic activity. This reflects Kazakhstan’s dependence on fossil fuels. The relationship between renewable energy and GDP is one-sided: GDP growth contributes to the development of renewable energy, but the reverse effect is not yet observed. Overall, the study highlights the energy dependence of the Kazakhstani economy and the need for policy to focus on energy efficiency and diversification of energy sources. This is an important step for the country’s sustainable and environmentally friendly development.